(untitled) (Journal of Face Aesthetics, 2024)
An important element in surgical aesthetic medicine is documentation, including the execution of photographic documentation at every important stage of treatment. Clinical photography is a common and appropriate form of documenting the face in procedural aesthetics. Photographs are considered an integral and necessary part of medical documentation moreover, it can be an important legal document. Instrumental studies, in the literature and in clinical practice, are still in the search for the most favorable algorithm that can serve as a standard technique recommended for practical use in surgical aesthetic medicine of the face. The case described here confirms the validity of photography and shows what possibilities and difficulties can be encountered in the analysis of instrumental documentation data.